Ultrafiltration rate and incident atrial fibrillation among older individuals initiating hemodialysis. Issue 11 (9th February 2021) - Flythe, Jennifer E; Liu, Sai; Montez-Rath, Maria E; Winkelmayer, Wolfgang C; Chang, Tara I
Abstract: Background: Higher ultrafiltration (UF) rates are associated with numerous adverse cardiovascular outcomes among individuals receiving maintenance hemodialysis. We undertook this study to investigate the association of UF rate and incident atrial fibrillation in a large, nationally representative US cohort of incident, older hemodialysis patients. Methods: We used the US Renal Data System linked to the records of a large dialysis provider to identify individuals ≥67 years of age initiating hemodialysis between January 2006 and December 2011. We applied an extended Cox model as a function of a time-varying exposure to compute adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for the association of delivered UF rate and incident atrial fibrillation. Results: Among the 15 414 individuals included in the study, 3177 developed atrial fibrillation. In fully adjusted models, a UF rate >13 mL/h/kg (versus ≤13 mL/h/kg) was associated with a higher hazard of incident atrial fibrillation [adjusted HR 1.19 (95% CI 1.07–1.30)]. Analyses using lower UF rate thresholds (≤10 versus >10 mL/h/kg and ≤8 versus >8 mL/h/kg, separately) yielded similar results. Analyses specifying the UF rate as a cubic spline (per 1 mL/h/kg) confirmed an approximately linear dose–response relationship between the UF rate and the risk of incident atrial fibrillation: risk began at UF rates of 6 mL/h/kg and the magnitude of this risk flattened, but remained elevated, at rates ≥9 mL/h/kg. Conclusion: In this observational study of older individuals initiating hemodialysis, higher UF rates were associated with higher incidences of atrial fibrillation.